A Voltage - Controlled Oscillator Aimed At Reducing Operational Failures And Resistant To Variations Of The Process, Voltage And Temperature - Gumroyan, H. V. («Պոլիտեխնիկ» տպ.)
A voltage - controlled oscillator resistant to variations of the process, voltage and temperature is presented. The proposed method allows to detect and compensate the control voltage value deviations due to the process variations. The system stabilizes the voltage value during the Voltage-Controlled Oscillator (VCO) operation and therefore improves the circuit reliability and reduces the parameter variability. The mixed-signal circuit is detecting the changes in input reference voltage values, and based on the deviation direction, reduces its impact. The compensation system is adjusting the reference signal value at the VCO operation start. The proposed system is compatible for most high-speed data links and is implemented with a standard VCO block. Ներկայացված է գործընթացի լարման և ջերմաստիճանի (ԳԼՋ) շեղումների նկատմամբ կայուն լարմամբ ղեկավարվող գեներատոր (ԼՂԳ): Առաջակվող համակարգը հնարավորություն է տալիս հայտնաբերել և կոմպենսացնել ԳԼՋ շեղումների հետևանքով առաջացող կառավարող լարման արժեքների տատանումները: Համակարգը կայունացնում է ԼՂԳ-ում լարման արժեքը և, հետևաբար, բարձրացնում է համակարգի հուսալիությունը և նվազեցնում պարամերտրերի փոփոխությունները: Խառը ազդանշանային սխեման հայտնաբերում է մուտքային հենակային լարման արժեքների փոփոխությունը և կախված դրա ուղղությունից՝ շտկում այն: Լարման ուղղման գործընթացը սկսվում է ԼՂԳ-ի աշխատանքի սկզբում: Առաջարկվող համակարգը կիրառելի է տվյալների փոխանակման արագագործ հանգույցներում և իրագործված է ստանդարտ ԼՂԳ համակարգի հիման վրա: Предлагается устойчивый к вариациям процесса, температуры и напряжения генератор частот, управляемый напряжением. Представленная система дает возможность обнаружить и компенсировать изменения управляющего напряжения, вызванные вариациями. Интегральная схема со смешанным сигналом обнаруживает изменения входного сигнала и в зависимости от направления изменения компенсирует его. Процесс исправления и стабилизации напряжения выполняется в самом начале работы генератора. Система сопоставима с большинством высокоскоростных систем передачи данных и реализована для стандартного генератора частот, управляемого напряжением.
Keywords: Microelectronics